Answer:
Explanation:
-2x + 3y – 4z = 8 ----------------(I)
5x – 3y + 5z = -8 -----------------(II)
7x – 3y + 3z = 8 ------------------(III)
Add equation (I) & (II) and thus y will be eliminated
(I) -2x + 3y – 4z = 8
(II) 5x – 3y + 5z = -8 {Add}
3x + z = 0 ------------------------(A)
Multiply equation (II) by (-1) and then add with equation (III). Thus y will be eliminated.
(II) * (-1) -5x + 3y - 5z = +8
7x – 3y + 3z = 8 {Add}
2x -2z = 16 ---------------(B)
Multiply equation (A) by 2 and then add. Thus z will be eliminated and we will get the value of x
(A) * 2 6x + 2z = 0
(B) 2x - 2z = 16 {Add}
8x = 16
Divide both sides by 8
x = 16/8
x = 2
Plugin x = 2 in equation (A)
3x + z = 0
3*2 + z = 0
6 + z = 0
z = -6
Plug in x = 2 and z = - 6 in equation (I)
-2x +3y - 4z = 8
-2*2 + 3y - 4*(-6) = 8
-4 + 3y + 24 = 8
3y + 20 = 8
3y = 8 - 20
3y = -12
y = -12/3
y = -4